Rice co-products in pig feed during the starter phase (15 to 30 kg) - De Oliveira Carvalho, Paulo Levi; De Lima Costa Filho, Clodoaldo; Gonçalves, Liliane Maria Piano; Pasquetti, Tiago Junior; Perondi, Dani [UNESP]; Huepa, Laura Marcela Diaz; Peñuela-Sierra, Lina María; Da Costa Oliveira, Aparecida; Carvalho, Silvana Teixeira; Genova, Jansller Luiz (Universidade Estadual de Londrina, 2018)
This study was carried out to evaluate the inclusion of two rice co-products in pig feed during the starter phase in terms of the nutritional value and digestibility of the co-products, and the effect on plasma parameters, growth performance and economic viability. In Experiment I, a digestibility assay was performed using 30 barrows (14.4 ± 2.4 kg body weight), which were distributed in a completely randomised design. The co-products studied were broken rice (BR) and hominy rice 3/4 (HR) to replace the reference diet (300 g/kg). The estimated digestible energy (DE) and metabolisable energy (ME) were 3,476 and 3,360 kcal/kg for BR and 3,487 and 3,362 kcal/kg for HR, respectively. In Experiment II, 108 pigs (15.5 ± 1.0 to 30.1 ± 1.3 kg body weight) were used, distributed in a randomised block design with a factorial analysis scheme (2 × 4), using two types of rice and four inclusion levels (160, 320, 480, and 640 g/kg), with six replicates and two pigs per experimental unit. Additionally, a control diet was used with no inclusion of the co-product. The daily weight gain increased and the feed:gain (F:G) ratio decreased as HR content of feed increased. An effect of both types of rice on plasma glucose concentration was obtained, in which the pigs fed with BR showed the highest values. The cost of diet per kilogram of body weight gain increased as BR levels in the diet increased. It was observed that inclusion levels of 480 and 640 g/kg of BR differed from the control diet, showing the highest costs. HR and BR can be used in pig feed in the starter phase at up to 640 g/kg without impairing performance.
Keywords: Co-product; Digestibility; Growth performance; Pigs